PROSES PEMBENTUKAN VERBA RESIPROKAL DALAM BAHASA MINANGKABAU DI KOTO TANGAH - Putri Maharani; Siti Ainim Liusti (Jurnal Bahasa dan Sastra, 2020)
The purpose of this study were (1) describe the process of forming reciprocal verbs, and (2) describe the meaning of reciprokal verbs in the Minangkabau language in the village of Koto Panjang Kecamatan Koto District Padang City. This type of research is a qualitative study using descriptive methods. The subject of this research is a speech that was obtained from an informant in the village of Koto Panjang Kecamatan Koto District Padang City which contains reciprocal verbs. Data were analyzed with the following steps: (1) transcribe data obtained from recordings, interviews, and observations into written language, (2) classify data based on the theory used, (3) analyzing and interpreting data based on the theory used, and (4) conclude the data. The results of this study are as follows. First, based on the process of formation, reciprocal verbs in the Minangkabau language used by people in the village of Koto Panjang Kecamatan Koto District Padang City can be classified into two types, (a) the process of forming reciprocal verbs through affixating, and (b) the process of forming reciprocal verbs through reduplicatison. Second, based on the meaning of reciprocal verbs obtained in the village of Koto Panjang Kecamatan Koto District Padang City found two, namely: (1) acts, and (2) conditions.